Housing conditions and housing finance for low-income households in Hanoi, Vietnam - Cu Huy Giai; Yap Koe Sheng; Weber, Karl E.; Lefebvre, B. G.; Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1992)
The thesis studied the housing development for low income people in Hano i Vietnam, with regard to housing finance and credit system for low income households. It was found that, due to economic difficulties State could not subsidize housing for all its employees . Most of them have to wait for a long time to get a house. The housing conditions of people in Hanoi, particularly low income households, worsen with time. The government had issued many measures for housing development such as State-and-People-Partnership, Housing for Sale, Self-Help Construction. However, due to fault in operation and management of above mentioned systems, and low income of households, most of households can not save money, so low income people in Hanoi is still facing housing problem. Up to 1986 in Vietnam the economic reform had opened new ways for the economic development, based on the multi-sector participation, with the goal to improve overall living condition for population. In this social-economic environment the Hanoi Bank for Housing Development ( HABUBANK ) had been established . It gives low income people of city a good opportunity in housing finance for themselves. Operation of HABUBANK is based on the housing business. Many of loans was contributed, which improved housing condition of low income people of city of Hanoi. However, the income of people still low, which was above mentioned, so Hanoi Bank for Housing Development have to allow loan to be small, so that poor people make required payment. Based on the study findings, the report recommendation immediate some measures to eliminate effectless housing development systems and to improve housing finance and credit system for low income households in Hanoi.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology
Keywords: Housing -- Vietnam -- Hanoi -- Finance